MoMih1 is indispensable for asexual development, cell wall integrity, and pathogenicity of Magnaporthe oryzae - Liu, Shiyi; Gong, Xinli; Ma, Ji; Wang, Shuaishuai; Guo, Min (Frontiers in Plant Science, 2023)
Asexual spore serves as essential inoculum of rice blast during the disease cycle, and differentiation of young conidium from conidiophore is intimately regulated by cell cycle. Mih1 encodes a dual-specificity phosphatase that involved in the G2/M transition of the mitotic cell cycle by regulating the Cdk1 activity in eukaryotes. Till now, the roles of Mih1 homologue, however, remain unclear in Magnaporthe oryzae. We here functionally characterized the Mih1 homologue MoMih1 in M. oryzae. MoMih1 is localized to both the cytoplasm and nucleus and can physically interact with the CDK protein MoCdc28 in vivo. Loss of MoMih1 led to delayed nucleus division and a high level of Tyr15 phosphorylation of MoCdc28. The MoMih1 mutants showed retarded mycelial growth with a defective polar growth, less fungal biomass, and shorter distance between diaphragms, compared with the KU80. Asexual reproduction altered in MoMih1 mutants, with both abnormal conidial morphogenesis and decreased conidiation. The MoMih1 mutants severely attenuated the virulence to host plants due to the impaired ability of penetration and biotrophic growth. The incapability of scavenging of host-derived reactive oxygen species, which was possibly ascribed to the severely decreased extracellular enzymes activities, were partially associated with deficiency of pathogenicity. Besides, the MoMih1 mutants displayed also improper localization of retromer protein MoVps26 and polarisome component MoSpa2, and defects of cell wall integrity (CWI), melanin pigmentation, chitin synthesis, and hydrophobicity. In conclusion, our results demonstrate that MoMih1 plays pleiotropic roles during fungal development and plant infection of M. oryzae.